The Forest for the Trees - Lerner, Betsy (New York : Riverhead Books, 2000)
"On May 29, 1990, Earth First! organizer Judi Bari's car was bombed in Oakland, California. Within three hours of the bombing, Bari was accused of transporting the explosives that had nearly killed her. Still in the hospital, she was arrested, and soon labeled a terrorist in the national media. The charges were later dropped. For the next twelve years, Bari and civil rights lawyer Dennis Cunningham would pursue a federal civil rights suit against the FBI and the Oakland police department. The Forest for the Trees, directed by Cunningham's daughter, is an intimate, behind-the-scenes look at Bari's fight, an important instance of the false and damaging association of dissent with crime and terrorism. At the heart of the film is Bari, a folk hero with an electrifying onscreen presence, and the legal battle that few believed she could win" -- From cover
Includes bibliographical references.
Director, Bernadine Mellis ; Executive producers, Judith Helfand and Julia Parker Benello ; Editor, Susan Korda ; Music, Jodi Berggren
Narrated by Bernadine Mellis
Grades 10-12, College, Adult
DVD
Keywords: Green movement -- History; Environmental justice; Environmental policy; Environmentalism -- Political aspects; Discrimination in criminal justice administration; Environmentalists; Forest conservation -- Citizen participation